Amyloid β-Related Angiitis Causing Coma Responsive to Immunosuppression - Shennan A. Weiss; David Pisapia; Stephan A. Mayer; Joshua Z. Willey; Kiwon Lee (Case Reports in Pathology)
Introduction. Amyloid-beta-related angiitis (ABRA) is a form of CNS vasculitis in which perivascular beta-amyloid in the intracerebral vessels is thought to act as a trigger for inflammation mediated by CD68+ macrophages and CD3+ T lymphocytes. Patients with severe ABRA may develop coma responsive to immunosuppressive treatment. Case Presentation. A 57-year-old man presented to the neurological intensive care unit febrile, obtunded, and with a left hemiparesis. He had suffered from intermittent left arm weakness and numbness for several months prior. Serum and cerebrospinal fluid studies showed a lymphocytic leukocytosis in the cerebrospinal fluid (CSF), but no other evidence of infection, and the patient underwent a brain biopsy. Histopathological examination demonstrated amyloid angiopathy, with an extensive perivascular lymphocytic infiltrate, indicative of ABRA. The patient was started on cyclophosphamide and steroids. Following a week of treatment he awakened and over several weeks made a significant neurological recovery. Conclusions. ABRA can have a variety of clinical presentations, including impairments in consciousness and coma. Accurate pathological diagnosis, followed by aggressive immunosuppression, can lead to impressive neurological improvements. This diagnosis should be considered in patients with paroxysmal recurrent neurological symptoms and an accelerated progression.